Incidence of surgical site infections in a tertiary hospital in Slovenia: Pogostnost pojavljanja okužb kirurške rane v terciarni bolnišnici v Sloveniji - Taskovska, Dragana; Flis, Vojko (Acta Medico-Biotechnica, 2021)
Purpose: Surveillance is an essential element of surgical site infection (SSI) prevention. Few studies have evaluated the long-term effect of these programs in Slovenia. SSIs are among the most commonly reported health care-associated infections, yet there is a paucity of data on SSI from Slovenia. We aimed to determine the incidence of SSI and explore its associated factors at a tertiary hospital in Slovenia.Methods: Direct and indirect surveillance methods, based on European Centre for Disease Control andPrevention guidelines, were used to define SSI. Patients were followed at 30 days and 1 year postoperatively. Demographic and medical data were collected and risk factors were assessed. Risk factors for SSI and the effect of surveillance time on SSI rates were statistically analyzed.Results: Of 8074 patients analyzed, the SSI rate was found to be 0.28%. One of the statistically significant risk factors for SSI included age (average age 66 years vs. 58 years: p=0.0206, t=2.315, p